The tale of the ungrateful grandfather - Rigby, Peter; Senyagwa, Gideon
The story presented here is very widespread in the oral literature o f the Wagogo people of Central Tanzania.
AR/MISR/34/1/5
English
Shelf no. 1.
Keywords: Short story